Charlotte Elizabeth Tonna and the mobilization of Tory women in early Victorian England - Gleadle, K (Cambridge University Press, 2007)
This article addresses the historiographical neglect of tory women in the early Victorian period. The existence of a vibrant culture of female conservative letters, combined with the widespread participation of women in ultra-Protestant pressure-group politics, is suggestive of the neglected contribution women made to the revival of grass-roots toryism during these years. In particular, it is suggested that a consideration of the distinctive features of premillenarian Evangelicalism enables a more discriminating approach to the impact of Evangelicalism upon contemporary women. By focusing upon the career of the prominent premillenarian Charlotte Elizabeth Tonna, and her editorship of the Christian Lady's Magazine, it is argued that contemporary attitudes towards 'female politicians' were far more flexible, variable, and contingent than is frequently assumed. The associational activities with which many premillenarians were involved, combined with their attention to Old Testament models of publicly active women and the sense of urgency that distinguished their theology, frequently led its adherents to problematize and critique existing formulations of women's roles.